History of depression but not current depression is associated with signs of atherosclerosis: data from the Gutenberg Health Study. Issue 5 (3rd July 2013) - Beutel, M. E.; Wiltink, J.; Kirschner, Y.; Sinning, C.; Espinola-Klein, C.; Wild, P. S.; Münzel, T.; Blettner, M.; Zwiener, I.; Lackner, K.; Michal, M.
Abstract : Objectives: To test the vascular depression hypothesis in the general population, we analyzed the association between current depression, medical history of depression, cognitive and somatic depressive symptom dimensions and measures of atherosclerosis [intima–media thickness (IMT) and carotid plaques]. Method: We included a representative sample of 5000 participants from the Gutenberg Health Study (GHS). Depression was assessed by the nine-item Patient Health Questionnaire (PHQ-9), and IMT and carotid plaques were measured at both common carotid arteries using an edge detection system. Regression analyses were performed separately for participants with and without cardiovascular disease, adjusting for medical history, cardiovascular risk factors and psychotropic medication. Results: Contrary to hypotheses, we found no increased IMT for somatic symptoms of depression; the same was true for depression and cognitive symptoms in the fully adjusted model. Only a moderate relationship between medical history of depression and the presence of atherosclerotic plaques was maintained after correction. Conclusions: The relationship between depression and atherosclerosis may be more complex than previously assumed. Although the vascular depression hypothesis was not supported, our results support the hypothesis that lasting depression leads to arteriosclerosis.